Evolução cromossômica em escorpiões brasileiros de gênero rhopalurus (buthidae) e espécies relacionadas - Ubinski, Crislaine Vanessa [UNIFESP] (2016)
Scorpiones has a great diversity of species and very particular chromosomal characteristics, such as holocentric and monocentric chromosomes, absence of genetic recombination during meiosis and great interspecific and intraspecific variation of diploid number. The family Buthidae is the most numerous among the Scorpiones, having more than 1.000 species taxonomically described, of which only 56 were studied under the cytogenetic view. Rhopalurus is the third most diverse genera from the Brazilian scorpion fauna, with nine species taxonomically described. Cytogenetically, only two species were examined, which showed the diploid number 2n=28. This aim of this work is to understand the processes related to chromosome differentiation in Brazilian species of Rhopalurus, Physoctonus and Troglorhopalurus. The chromosomes were standard-stained using 3% Giemsa solution, silver-impregnated to detect the nucleolar organizer regions (NORs), and submitted to fluorescence in situ hybridization (FISH) technique to localize the 28S rDNA and (TTAGG)n telomeric sites. The analysis of mitotic and meiotic cells in all species revealed holocentric chromosomes and following diploid number: 2n=28 in Rhopalurus agamemnon, Rhopalurus pintoi and Rhopalurus rochai; 2n=26 in Physoctonus debilis, Rhopalurus sp.n.1 and Rhopalurus sp.n.2; 2n=25 in Rhopalurus guanambiensis; 2n=22 in Rhopalurus crassicauda; 2n=20 in Troglorhopalurus translucidus; and 2n=20-22 in Rhopalurus lacrau. These results reveal that number diploid higher than 2n=20 is a common feature among the species of this group, as it occurs in most genera of Buthidae. Prophase I spermatocytes exhibited the synaptic and achiasmatic chromosome behaviour and formation of multivalent association in Rhopalurus crassicauda, Rhopalurus guanambiensis, Rhopalurus pintoi and Rhopalurus sp.n.2. These multivalent associations probably were consequence of reciprocal translocations or fission/fusion chromosomal rearrangements. In prophase I cells of one female of Troglorhopalurus translucidus, we verified bivalents with similar behavior to that observed in males of scorpions, indicating the absence of genetic recombination in meiosis. Despite the intraspecific variation of diploid number, most species analyzed in this work presented a conserved pattern of two NORs and 28S rDNA cistrons, localized in terminal region of the chromosomes. The presence of (TTAGG)n telomeric repeats was observed in the 10 species studied, occurring only in terminal regions of the chromosomes, including the specimens carriers of the heterozygous chromosome rearrangements.